PENGARUH AKUNTABILITAS, TEMUAN AUDIT DAN TINDAK LANJUT HASIL AUDIT TERHADAP TINGKAT KORUPSI - Wiwin Aminah (JAF (Journal of Accounting and Finance), 2020)
This study aims to detemine the effect of accountability, audit findings, and follow-up on audit results on the level of corruption in West Java Provinces periods of 2017-2018. The results showed that accountability, audit findings and follow-up to audit results had a simultaneous effect on the level of corruption. Partially the follow-up of audit results has a negative effect on the level of corruption, while accountability and audit findings do not have a significant effect on the level of corruption. The results of this study are expected to contribute in the form of empirical evidence that supports or rejects the results of previous research and provides input for policy makers who will be considered in preventing corruption in West Java Province and can describe each of the factors of Accountability, Audit Findings and Audit Follow-up and find the influence of each of these factors on the level of corruption in West Java.